The Influence of Capital Structure and Level of Liquidity on Company Financial Performance With Firm Value As An Intervening Variable (Study on Manufacturing Companies listed on the Indonesia Stock Exchange in the Textile and Garment Industry Sector for the period 2020-2023) - Puhut Bona Lucky, Joel; Setiawan, Andy (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study focuses on observing the effect of capital structure and liquidity level in the company's financial performance during the COVID-19 period by using firm value as an intervening variable. This research uses a quantitative approach by testing hypotheses. The population taken in this study are companies engaged in the textile and garments sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The research sample used used purposive sampling method and resulted in 16 company samples. The results of this research analysis show that capital structure and liquidity have an insignificant effect on financial performance and firm value cannot intervene in the relationship between the dependent variable and the independent variable.